2023
DOI: 10.1111/rec.13853
|View full text |Cite
|
Sign up to set email alerts
|

Ant and plant diversity respond differently to seed‐based prairie restoration

Abstract: Recovering biodiversity is a common goal of restoration, yet outcomes for animal communities are highly variable. A major reason for this variability may be that active restoration efforts typically target plant communities, with the assumption that animal communities will passively recover in turn. However, this assumption remains largely unvalidated experimentally making it unclear how plant-focused restoration strategies influence animal communities. We evaluated how the diversity of seed mixes used to rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Contrary to our expectations, we did not find a clear effect of seed mix richness or admixture seed sourcing on floral species richness. Previous research has found that seed mix richness increased plant diversity (Larson et al., 2011), but responses can be highly variable (Paraskevopoulos et al., 2022). Although many of the target species in the seed mixes established, we observed high numbers of unsown species in the prairies, and these may have swamped out differences in sown seed richness.…”
Section: Discussionmentioning
confidence: 98%
“…Contrary to our expectations, we did not find a clear effect of seed mix richness or admixture seed sourcing on floral species richness. Previous research has found that seed mix richness increased plant diversity (Larson et al., 2011), but responses can be highly variable (Paraskevopoulos et al., 2022). Although many of the target species in the seed mixes established, we observed high numbers of unsown species in the prairies, and these may have swamped out differences in sown seed richness.…”
Section: Discussionmentioning
confidence: 98%
“…In this case further management interventions may be needed, these could take the form of translocations or seeding. These interventions have been shown to increase the establishment of native plant species in restored sites (Orrock et al, 2023), and have also been shown to influence the structure of non‐plant species communities (Paraskevopoulos et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Forested and open habitats tend to have strongly differing ant communities (Andersen, 1997(Andersen, , 2019Lassau & Hochuli, 2004;Resasco & Fletcher, 2021), which we see represented in the differences between the north-and south-facing slope assemblages. Horizontal vegetation cover has been shown to have a negative relationship with ant species richness (Lubertazzi & Tschinkel, 2003;Muluvhahothe et al, 2021;Paraskevopoulos et al, 2023). However, vegetation cover may explain the increased site occurrence of common generalist species (Retana & Cerd a, 2000).…”
Section: Tree Covermentioning
confidence: 99%